Pentalogy of Fallot: A case report - Zhixiong Zhong; Ting Wen (Journal of International Medical Research)
We report the case of a 45-year-old woman with pentalogy of Fallot, a severe and complicated cyanotic congenital heart disease. Congenital anomalies of pentalogy of Fallot include ventricular septal defect, right ventricular hypertrophy, saddle aorta, pulmonary ostium stenosis, atrial septal defect, and patent foramen ovale. Pentalogy of Fallot is less common than triplet and tetralogy of Fallot and can affect children’s physical development. Approximately 95% of patients with pentalogy of Fallot die before the age of 40 years, and early surgical radical surgery is recommended. However, the patient in the current case did not undergo surgery.